2014
DOI: 10.2527/jas.2013-7226
|View full text |Cite
|
Sign up to set email alerts
|

Effect of graded inclusion of dietary soybean meal on nutrient digestibility, health, and metabolic indices of adult dogs1

Abstract: Two studies were conducted using adult dogs to evaluate the effect of increasing the inclusion of soybean meal (SBM) in an adult dog food on body composition, hematological and biochemical blood analyses, and total tract nutrient digestibility. Nutritionally complete and balanced diets were formulated with commercial-grade SBM (48% CP) to replace 0, 10, 20, or 30% of the protein provided by dried chicken protein resulting in final SBM inclusion of 0, 6.0, 11.5, and 17.0% (as-fed basis), respectively. In study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…In vitro lipid digestibility of a sample of wet canned food for adult dogs as determined using different combinations of gastric lipase and emulsifiers and literature data. The dotted line indicates the mean of results drawn from the literature (Dust et al 2005;Yamka et al 2006;Vhile et al 2007;Kempe and Saastamoinen, 2007;Guevara et al 2008;Barry et al 2009;Dobenecker et al 2010;Brambillasca et al 2010;Hendriks et al 2013;Menniti et al 2014) while the solid line indicates results obtained with the technique proposed by Vervaeke et al (1989) with no addition of gastric lipase and emulsifiers. BS: Bile salts (cholic acid-deoxycholic acid sodium salt mixture); Tw20: Polysorbate 20 (polyoxyethylene sorbitan monolaurate; Tween 20, Sigma Aldrich); L: Gastric lipase.…”
Section: Validation Of the In Vitro Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro lipid digestibility of a sample of wet canned food for adult dogs as determined using different combinations of gastric lipase and emulsifiers and literature data. The dotted line indicates the mean of results drawn from the literature (Dust et al 2005;Yamka et al 2006;Vhile et al 2007;Kempe and Saastamoinen, 2007;Guevara et al 2008;Barry et al 2009;Dobenecker et al 2010;Brambillasca et al 2010;Hendriks et al 2013;Menniti et al 2014) while the solid line indicates results obtained with the technique proposed by Vervaeke et al (1989) with no addition of gastric lipase and emulsifiers. BS: Bile salts (cholic acid-deoxycholic acid sodium salt mixture); Tw20: Polysorbate 20 (polyoxyethylene sorbitan monolaurate; Tween 20, Sigma Aldrich); L: Gastric lipase.…”
Section: Validation Of the In Vitro Methodsmentioning
confidence: 99%
“…Dust et al 2005;Yamka et al 2006;Vhile et al 2007;Kempe and Saastamoinen, 2007;Guevara et al 2008;Barry et al 2009;Dobenecker et al 2010;Brambillasca et al 2010;Hendriks et al 2013;Menniti et al 2014. Kempe and Saastamoinen, 2007;Guevara et al, 2008;Barry et al 2009;Dobenecker et al 2010;Brambillasca et al 2010;Hendriks et al 2013;Menniti et al 2014. (r 2 ¼ .95) between in vivo and in vitro organic matter digestibility despite the fact that their method did not involve the utilisation of gastric lipase and bile salts (however, the last step of the method that they proposed involves washing the undigested residue with ethanol and acetone, two organic solvents which are very likely to remove all the undigested fat). Based on our own results, the digestibility of lipids is strongly underestimated if gastric lipase and bile salts are not used and this is very likely to lead to an underestimation of the digestible energy of food.…”
Section: Validation Of the In Vitro Methodsmentioning
confidence: 99%
“…As regards the digestibility coefficient ( Table 5 ), in most studies, the inclusion of soybean meal reduced the ADC of DM [ 9 , 13 , 22 , 28 , 30 , 32 ], EE [ 3 , 27 , 28 , 30 ] and GE [ 22 , 27 , 30 ] and increased the ADC of CP [ 3 , 24 , 27 , 29 ]. Of the 13 articles cited, 7 [ 10 , 22 , 24 , 26 , 27 , 32 , 34 ] presented the metabolizable energy (ME) values of the diet and, within these studies, soybean meal inclusion reduced ME.…”
Section: Resultsmentioning
confidence: 99%
“…Only one study [ 33 ], in which different inclusion levels were tested, showed opposite results, i.e., when the level of inclusion of the ingredient was increased, the ADC of DM decreased, whereas when its inclusion level was reduced, the ADC of DM increased. The ADC of CP was the variable that most varied in the results: 4 articles reported no statistical differences [ 10 , 13 , 31 , 34 ]; another 4 [ 3 , 25 , 27 , 29 ] showed reduced digestibility; and only one [ 9 ] described an increase in the coefficient. Results were divergent in only two articles [ 12 , 33 ], in which the authors compared increasing levels of inclusion and observed that higher levels resulted in increased digestibility of the ingredient, whereas lower levels induced a reduction in the ADC of CP.…”
Section: Resultsmentioning
confidence: 99%
“…As an example, soybean meal is derived from defatted soybeans and has an AA profile similar to pulses. In a 24-wk study that evaluated graded concentrations of soybean meal up to 17% (as-fed basis) in dog foods, soybean meal inclusion did not affect the nutrient status of dogs as indicated by serum biochemistry analysis (Menniti et al, 2014). However, Yamka et al (2003) demonstrated that using soybean meal at more than 15% inclusion on a dry matter basis decreased crude protein digestibility.…”
Section: Introductionmentioning
confidence: 99%